Implementation Of The Inquiry Learning Learning Model To Develop Students' Critical Thinking Abilities In The Ppkn Subject For Grade X - Canra Suzana Hutapea; Hotmaida Simanjuntak; Kondios Mey Darlin Pasaribu (STABN RADEN WIJAYA WONOGIRI, 2025)
This study aims to determine Implementation of the Inquiry Learning Model to Develop Students' Critical Thinking Skills in the Civics Subject of Grade X Students of Sma Negeri 1 Borbor. Based on the results of research and discussion regarding the implementation of the Inquiry Learning model on students' critical thinking skills in the Civics subject in grade X of Sma Negeri 1 Borbor, it can be concluded that the implementation of the Inquiry Learning model has a significant influence on improving students' critical thinking skills. This is evidenced by the results of the pretest and posttest data analysis which show that the initial abilities of students in the experimental class and the control class are at a relatively similar level. However, after being given treatment, the experimental class using the Inquiry Learning model experienced a much higher average increase in scores compared to the control class using conventional learning methods. This difference is reinforced by the results of the hypothesis test which shows a significance value of less than 0.05, so it can be stated that there is a significant difference between the two groups after the treatment is given. Overall, this study proves that the Inquiry Learning model is able to create a more active, interactive, and student-centered learning process, so it can improve critical thinking skills in Civics learning